The effect of shoulder position difference of streamline posture in competitive swimmers - Watanabe, Y.; Wakayoshi, K.; Normura, T. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The objective of this study was to investigate the movements of the centers of buoyancy and mass and the change in the distance between the two centers because of the elevation of the shoulder joints. The total length increased by 5.7 em on an average because of the elevation of the shoulder joints. The positions of the center of mass with respect to the heels were 103.4 & 4.0 cm during depression and 104.2 i 4.1 cm during elevation. The center of buoyancy shifted toward the head more during elevation (105.9 i 4.2 cm) than during depression (105.1 * 4.1 em) during neutral buoyancy. Also, the distance between the centers of buoyancy and mass was smaller during elevation (1.60 * 0.20 cm) than during depression (1.66 * 0.21 cm) with 1% significance. This study suggests a possible effect of the shoulder position on maintaining a horizontal position.